Competencies essential for nursing care : skill guide part II (Malabon City, Philippines : Guiani Prints House, 2003)
Professional nursing as an art and science continue to challenge nurse educators and practitioners in providing quality care.
Part I - Drug administration -- Part II - Care of patients undergoing surgery -- Part III - Assisting patients with respiration -- Part IV - Assisting patient with intravenous therapy -- Part V - Nutrition and metabolism -- Part VI - Assisting patients with elimination.
Includes bibliographical references.
Keywords: NURSING